2020
DOI: 10.21273/hortsci15200-20
|View full text |Cite
|
Sign up to set email alerts
|

Longer Photoperiods with the Same Daily Light Integral Improve Growth of Rudbeckia Seedlings in a Greenhouse

Abstract: Supplemental light can increase growth and accelerate production of greenhouse crops, but it can be expensive if not provided in a way that promotes efficient use of the light. Dimmable light-emitting diode (LED) fixtures have the potential to reduce lighting costs because the output can be precisely controlled to meet crop needs. Because light is used more efficiently to drive photosynthesis at lower photosynthetic photon flux densities (PPFDs), we hypothesized that providing Rudbeckia fulgida var. sullivanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
4
31
1
Order By: Relevance
“…Lower PPFDs combined with longer photoperiods increased CCI, canopy light interception, and Φ PSII . The observed increase in growth under lower PPFDs and longer photoperiods is consistent with prior studies, which found that when DLI is held constant, plants generally produce more biomass when grown under longer photoperiods [7][8][9]11,12,39,40]. The observation that spreading a given DLI over a longer photoperiod with a lower instantaneous PPFD has clear benefits to growers; first, the initial capital expenses can be reduced because fewer lighting fixtures are needed to provide the lower PPFD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lower PPFDs combined with longer photoperiods increased CCI, canopy light interception, and Φ PSII . The observed increase in growth under lower PPFDs and longer photoperiods is consistent with prior studies, which found that when DLI is held constant, plants generally produce more biomass when grown under longer photoperiods [7][8][9]11,12,39,40]. The observation that spreading a given DLI over a longer photoperiod with a lower instantaneous PPFD has clear benefits to growers; first, the initial capital expenses can be reduced because fewer lighting fixtures are needed to provide the lower PPFD.…”
Section: Discussionsupporting
confidence: 87%
“…Taking advantage of dimmable LED fixtures, we previously conducted greenhouse trials where plants in different treatments all received the same DLI, but spread out over photoperiods ranging from 12 to 21 h. The shoot and root dry mass of Rudbeckia fulgida var. sullivantii seedlings increased by 30 and 24%, respectively, as the photoperiod increased from 12 to 21 h [11], while lettuce shoot dry mass increased by 28% [12]. Under sole-source lighting, the effect of longer photoperiods, with the same DLI, on the growth of lettuce may be greater when that DLI is higher [13], consistent with the finding that the total daily electron transport rate through photosystem II responds more strongly to longer photoperiods when the DLI is higher [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a study that improved radiation capture by replacing blue light with far-red light, which increased the biomass of kale and lettuce due to increased leaf size [ 29 ]. Improving canopy size early in the plant’s growth and development is of benefit to growers, as seedlings capture little supplemental light due to their small size [ 54 ]. A larger canopy size allows plants to capture more light to drive growth, as light interception is a major determining factor for carbon gain.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their small canopy size, seedlings capture only a small fraction of the provided light. Therefore, increased PCS at early stages can increase light capture and growth of seedlings [ 11 ]. A previous study compared different lettuce cultivars and found that early PCS was a good predictor of final shoot biomass [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combining those data with PPFD data allows for estimation of the total incident light over the course of the growing cycle. Projected canopy size is also valuable to make crop growth predictions, since PCS early in the growing cycle may be correlated with the final dry weight of the crop, as we have previously shown in lettuce ( Lactuca sativa ) [ 6 , 10 ] and black-eyed susan ( Rudbeckia fulgida ) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%